Spermatozoa Quality of Kampung Unggul Balitbangtan (KUB) Chicken at 5oC Storage Supplemented with Glucose in Liquid Semen Diluent - J. Junaedi; Nurul Isnaini; Muhammad Halim Natsir; I. Iswati; Trinil Susilawati (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
This research was conducted to determine the effect of glucose supplementation in liquid semen diluent on the quality of Kampung Unggul Balitbangtan (KUB) spermatozoa.The chicken used is KUB chicken as many as 8 tails.The research procedure consists of; the manufacture of diluent, collection of semen, dilution of semen, storage, and evaluation of semen.Evaluation of semen was carried out on motility, viability, abnormalities, and plasma membrane integrity at 0 and 3 days of storage.Data were analyzed using the T-test to compare the quality of spermatozoa with added glucose into the liquid semen diluent and without the addition of glucose.The addition of glucose into the diluent was able to maintain spermatozoa motility at 35.00 ± 11.50, spermatozoa viability at 41.42 ± 10.15, and spermatozoa plasma membrane integrity at 82.94 ± 7.42 at 5oC storage for three days.This study concluded that glucose supplementation into liquid semen diluent was able to maintain plasma membrane motility, viability, and integrity at 5oC storage for three days, spermatozoa quality of KUB chickens was able to survive at 5oC storage for three days, and glucose can be added to the liquid semen diluent at a dose of 10 mM.